2020
DOI: 10.1108/ijssp-07-2020-0289
|View full text |Cite
|
Sign up to set email alerts
|

Machiavellianism, locus of control, moral identity, and ethical leadership among public service leaders in Malaysia: the moderating effect of ethical role modelling

Abstract: PurposeThe objective of this study is to examine the predicting role of Machiavellianism, locus of control and moral identity on ethical leadership. This study also assessed the moderating role of ethical role modelling in the linkage between Machiavellianism, locus of control, moral identity and ethical leadership.Design/methodology/approachA total of 202 public service leaders in Malaysia participated in the study. A quantitative study was conducted and structural equation modelling was used to test the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Ethical leadership has the feature of altruistic attention, that is, the leaders treat subordinates generously and amicably, care about subordinates and pay attention to their interests. Previous studies have shown that the leaders' altruistic behaviours help establish a good relationship with subordinates, and this relationship will promote employees to actively participate in innovative activities and accept risky and challenging tasks more easily (Basu and Green, 1997;Tierney et al, 1999;Tierney, 1992;Zainun et al, 2021). In addition, ethical leaders have the character of collective motivation.…”
Section: Research Modelmentioning
confidence: 99%
“…Ethical leadership has the feature of altruistic attention, that is, the leaders treat subordinates generously and amicably, care about subordinates and pay attention to their interests. Previous studies have shown that the leaders' altruistic behaviours help establish a good relationship with subordinates, and this relationship will promote employees to actively participate in innovative activities and accept risky and challenging tasks more easily (Basu and Green, 1997;Tierney et al, 1999;Tierney, 1992;Zainun et al, 2021). In addition, ethical leaders have the character of collective motivation.…”
Section: Research Modelmentioning
confidence: 99%
“…According to the locus of control theory [ 29 ], individuals’ control of their living environment and events is the primary motivation for behavior. Individuals with a relatively high sense of control have stronger autonomy and efficiency, and a lack of control can lead to psychological problems such as depression [ 30 ]. Moreover, high self-control is one of the protective factors of life satisfaction [ 31 ] whereas low self-control can negatively affect adolescents’ psychology health and overall well-being [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theories on fraud, weaknesses on public procurement, emergence of online attacks such as cyber fraud and cybercrime seem to be the areas discussed in those studies (Bakri and Said, 2017;Zainun et al, 2020;Akenroye, 2013;Flynn and Harris, 2022;Owusu et al, 2021;Rustiarini et al, 2019;Azmi et al, 2017;Zaharon, 2021;Singh et al, 2021;Alam and Said, 2015;Ahmi et al, 2014;Mohammad et al, 2022;Lagazio et al, 2014)…”
Section: Fraud Prevention and Detection Mechanismsmentioning
confidence: 99%